Ukrainian agro-food sector in the context of global patterns of environmental innovation development - Boris Burkinsʹkij; Larysa Kupinets; Natalya Andryeyeva; Olha Shershun (Comparative Economic Research. Central and Eastern Europe, 2022)
The structure of the process of introducing innovative technologies in the agricultural sector, the competitive position of Ukraine in the world rankings of the development of agricultural science and training of personnel for the needs of the agro-industrial complex are considered and analyzed. Scientific and patent-investment activities of enterprises of the agro-industrial complex of Ukraine are studied. The methodology of bringing the mechanism of analytical and statistical observation of the state of innovative economic development in line with the standards of the Organization for Economic Cooperation and Development and the EU is analyzed. The main strengths and weaknesses of innovative activity of the agricultural sector of Ukraine are identified. As a result of the study, the authors propose adaptive changes in the process of implementing environmental innovations in the rational use of natural resources in the agricultural sector.
Keywords: O32; Q13; Q16; Q56; 330; agro-industrial complex; innovation; statistic; sustainable development; expenditure